2015
DOI: 10.1182/blood-2014-08-595801
|View full text |Cite
|
Sign up to set email alerts
|

Durable remissions in a pivotal phase 2 study of brentuximab vedotin in relapsed or refractory Hodgkin lymphoma

Abstract: Key Points• A total of 47% of patients who achieved CR on brentuximab vedotin remain progression-free after being followed a median of 53 months.• Younger age, less functional impairment, and lower disease burden at baseline were associated with CR and prognostic for longer survival.We present response and survival outcomes of a pivotal phase 2 trial of the antibody-drug conjugate brentuximab vedotin in patients with relapsed/refractory Hodgkin lymphoma following autologous stem cell transplant (N 5 102) after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
140
2
15

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 202 publications
(161 citation statements)
references
References 31 publications
4
140
2
15
Order By: Relevance
“…BV may represent an optimal therapeutic candidate and displays a number of features favoring its use as a bridge to ASCT in HL patients achieving a suboptimal response to salvage treatment [19,32]. First, it has a toxicity profile that does not overlap with most agents used in conditioning regimens.…”
Section: Discussionmentioning
confidence: 99%
“…BV may represent an optimal therapeutic candidate and displays a number of features favoring its use as a bridge to ASCT in HL patients achieving a suboptimal response to salvage treatment [19,32]. First, it has a toxicity profile that does not overlap with most agents used in conditioning regimens.…”
Section: Discussionmentioning
confidence: 99%
“…Результаты исследования сообщаются в 3 публикациях [6,14,15] Медиана времени до достижения ответа составила 5,7 недель, до полного ответа -12 недель. Это соответ-ствует 2 и 4 циклу терапии БВ.…”
Section: эффективность терапии брентуксимабом ведотином у разных попуunclassified
“…В качестве сравнения были взяты БВ, ХТ±ЛТ и ХТ±ЛТ с намерением проведения ал-лоТСК. Данные об эффективности БВ были взяты из ис-следования SG035-0003 [14,15].…”
Section: фармакоэкономические исследованияunclassified
“…Longer-term follow-up from this study has shown that the responses have been very durable. Of the 34 patients who achieved a complete remission, 47% remain progression free with a median follow-up of 53.3 months [23].…”
Section: Brentuximab Vedotinmentioning
confidence: 99%